Genetic diversity of Rhizophora mucronata in eastern region of Timor Island, Indonesia as revealed by RAPD - Ihwan Ihwan; uslan uslan; nashi widodo; Luchman Hakim (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ihwan, Uslan, Widodo, Hakim L. 2019. Genetic diversity of Rhizophora mucronata in eastern region of Timor Island, Indonesia as revealed by RAPD. Biodiversitas 20: 3364-3371. Mangrove ecosystems have essential functions in producing organic materials, protecting against erosion, and supporting the area between land and sea. Rhizophora mucronata is a dominant mangrove species in all coastal areas of Timor Island, East Nusa Tenggara, Indonesia. Recent reports suggest that mangroves have been affected by anthropogenic pressure and natural disasters. The aim of this study was to determine the genetic diversity of R. mucronata in the east region of Timor Island. This study is important in supporting mangrove protected management planning in the region. The sampling was carried out in six mangrove vegetation sites, DNA was isolated from the leaves and used for PCR-RAPD using six primers. Dendrogram analysis of the species was determined based on UPGMA (unweighted pair group method) and the similarity coefficient from Nei and Li using the MVSP program. The results showed that the six primers used generated a DNA length of 270-1345 bp, with the number of bands being 22-27. The percentage of polymorphism ranged from 73.91% to 86.96% in all primers used, with a polymorphic information content (PIC) value of 0.94. Thus, it can be concluded that the value of genetic diversity (He) from the R. mucronata mangrove population in Timor Island has a value of 0.666. The R. mucronata population in Abudenok and Tanjung Bastian has the highest genetic diversity with a value of 0.667, while the population in Tanjung Tuamese has the lowest genetic diversity with a value of 0.664. Based on the results of the dendrogram analysis, the R. mucronata population in Timor Island correlated with its geographical location. The adjacent populations have a tendency to form one subgroup.